2000
DOI: 10.1136/bmj.321.7274.1445
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of galantamine in patients with mild to moderate Alzheimer's disease: multicentre randomised controlled trial

Abstract: Objective To evaluate the efficacy and safety of galantamine in the treatment of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
402
2
13

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(441 citation statements)
references
References 30 publications
24
402
2
13
Order By: Relevance
“…In one study of another cholinesterase inhibitor (galantamine), placebo-treated carriers and noncarriers showed similar cognitive decline over 6 months, 14 while in another similar study carriers showed greater deterioration than noncarriers. 15 A tacrine study that demonstrated less cognitive decline in APOE e4 carriers than in noncarriers, especially in women, over 30 weeks, 16 was consistent with the current 6-month rivastigmine study which shows a tendency for noncarriers taking placebo to have a greater cognitive decline than carriers. The source of these disparate results is not known.…”
Section: Discussionsupporting
confidence: 66%
“…In one study of another cholinesterase inhibitor (galantamine), placebo-treated carriers and noncarriers showed similar cognitive decline over 6 months, 14 while in another similar study carriers showed greater deterioration than noncarriers. 15 A tacrine study that demonstrated less cognitive decline in APOE e4 carriers than in noncarriers, especially in women, over 30 weeks, 16 was consistent with the current 6-month rivastigmine study which shows a tendency for noncarriers taking placebo to have a greater cognitive decline than carriers. The source of these disparate results is not known.…”
Section: Discussionsupporting
confidence: 66%
“…In both cases this leads to an augmentation in the availability of the neurotransmitter acetylcholine. They are attributed with a 'significant, although modest, effect on the cognitive status of patients with AD' (Grutzlender and Morris, 2001), and include the plant-(snowdrop and daffodil bulb) derived drug galantamine (Wilcock et al, 2000). However, these alkaloid drugs can be toxic, offering a narrow therapeutic window, and are often associated with a number of deleterious side effects.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Several studies did not find that APOE genotype influenced treatment response. [21][22][23][24][25][26][27][28] Gender, either alone or in interaction with APOE genotype, was not found to influence response to ChEIs. 18,23,26,27 Several lines of evidence indicate that butyrylcholinesterase (BuChE) has a significant role in cholinergic function, both in the normal brain and in AD.…”
Section: Introductionmentioning
confidence: 99%